Composite membrane containing graphene oxide in sulfonated polyether ether ketone in microbial fuel cell applications. (21st September 2015) - Leong, Jun Xing; Daud, Wan Ramli Wan; Ghasemi, Mostafa; Ahmad, Azizan; Ismail, Manal; Liew, Kien Ben
Abstract: In this study, a single layer graphene oxide is successfully synthesized and used as a nano-filler in a self-fabricated sulfonated polyether ether ketone (SPEEK) to make a composite proton exchange membrane, graphene oxide/SPEEK (GO-SPEEK). The properties of GO-SPEEK, Nafion ® 117 and SPEEK are then compared to ascertain their selectivity to proton transport compared to both water and oxygen. GO-SPEEK was found to have the highest selectivity with a water uptake of 85.4%, proton conductivity of 1.48 × 10 −3  S cm −1 and oxygen diffusion coefficient of 1.154 × 10 −6 cm 2 s −1 . During tests in Microbial Fuel Cells (MFCs), the MFC system with Nafion ® 117 membrane produces the highest maximum power density (1013 mW m −2 ) followed by the MFCs with GO-SPEEK (902 mW m -2 ) and SPEEK (812 mW m −2 ) membranes. On the other hand, the MFC with GO-SPEEK membrane produces the highest coulombic efficiency (16.88%). The high efficiency and comparable maximum power density which is produced by the MFC with GO-SPEEK membrane, shows that GO-SPEEK membrane is a promising alternative membrane to replace the expensive Nafion ® 117 as a separator in the MFC. Highlights: Graphene oxide/SPEEK composite membrane was synthesized and characterized. Graphene oxide nano-filler increased proton conductivity and reduced oxygen crossover. Graphene oxide/SPEEK composite membranes are good separators for MFCs.